Digital visual culture [ theory and practice - Bentkowska-Kafel, Anna; Cashen, Trish; Gardiner, Hazel (Computers and the history of art, 2009)
Since its inception in 1985, CHArt - Computers and the History of Art - has been at the forefront of international debate on digital art practice, curation and scholarship. This title includes papers